Thienopyridine reloading in clopidogrel-loaded patients undergoing percutaneous coronary interventions: The PRAISE study. (1st November 2016) - Guo, Long Zhe; Kim, Moo Hyun; Shin, Eun Seok; Ann, Soe Hee; De Jin, Cai; Cho, Young-Rak; Park, Jong Sung; Park, Kyungil; Park, Tae-Ho; Lee, Michael S.; Serebruany, Victor L.
Abstract: Objective: The impact of thienopyridine reloading on clinical outcomes, and residual high platelet reactivity (HPR) is unclear. We sought to compare the HRP-related effect of prasugrel and clopidogrel reloading in the already clopidogrel-loaded patients undergoing percutaneous coronary intervention (PCI). Materials and methods: In this prospective, two-center, randomized, open-label study, patients with HPR who had undergone PCI after a clopidogrel (300–600 mg) loading dose (LD) were enrolled. Among screened (n = 153), HPR was determined in seventy-six patients, who were randomized to either repeated clopidogrel (300 mg LD, followed by 75 mg MD daily) or prasugrel (20 mg LD, followed by 5 mg MD daily). The primary endpoint was HPR at 24 h after PCI, as determined by the VerifyNow assay. The rates of sustained high and low platelet reactivity, periprocedural myocardial injury (PMI) and 30-day clinical outcomes were also assessed. Results: Higher inhibition of platelet reactive units (PRU) was observed in the prasugrel group than after clopidogrel reloading (Pre-PCI: 284.4 ± 32.0 vs 279.5 ± 32.5, p = 0.504; Post-PCI: 100.0 ± 67.0 vs 202.9 ± 65.8, p < 0.001; 30 days: 170.8 ± 69.8 vs 215.1 ± 62.4, p = 0.007). There were less HRP post-PCI after prasugrel compared with the clopidogrel group (2.7 vs 36.1%, p < 0.001). However, reloading with prasugrel did not reduce PMI compared to clopidogrel (36.8% vs 39.5%, p = 0.813). Conclusion: Prasugrel reloading led to a greater reduction in HPR, but similar with clopidogrel PMI in post-PCI patients. Larger randomized evidence is needed for optimization of loading strategies with thienopyridines. Clinical Trial Registration Information:NCT01609647 .